Change of human rights perspective in Iran - Davoodifard, Hassan; Jawan, Jayum (Center for Promoting Ideas, 2011)
This article departs from the Universal, Cultural Relativism, and Islamic perspective of human rights and defends the Universal perspective of human rights in general. It will discuss how the debate of human rights in Iran is as ongoing struggle between Iranian government and its populations. It focuses on the debate of women rights and the freedom of media (Internet) in current policies of Iranian government. And then introduce some evidence related to vulnerability of Iranian government because of new human rights movement, to show that changing of IRI’s human rights perspective is occurring.